PENDEKATAN PROBLEM BASED-LEARNING DALAM PENGEMBANGAN PETUNJUK PRAKTIKUM IPA UNTUK SMP/MTS KELAS VIII - Syakur, Akhmad; Rahmat, Irwandi; Hatta, A. Afrinaramadhani; Alqadri, Zulqifli; Yani, Ahmad (Jurnal Biogenerasi, 2024)
This study aims to develop a problem-based science practicum guide intended for grade VIII junior high school students in the first semester. The problem-based approach was chosen because it has proven effective in enhancing students' critical thinking and problem-solving skills. This research employed the 4D method, encompassing the stages of Define, Design, Develop, and Disseminate. The findings indicate that the problem-based practicum guide developed meets the criteria for validity, practicality, and effectiveness. The validity score reached 4.2, indicating it meets the valid criteria, while the practicality score reached 4.6, classifying it as practical. Additionally, the guide’s effectiveness is demonstrated by a positive student response rate of 84.8%. The final product from this research is expected to serve as a reference for teachers in conducting problem-based science learning, thereby supporting improvements in the quality of science education in schools.